A complete workflow for single cell mtDNAseq in CHO cells, from cell culture to bioinformatic analysis - Foley, Alan; Lao, Nga; Clarke, Colin; Barron, Niall (Frontiers in Bioengineering and Biotechnology, 2024)
Chinese Hamster Ovary (CHO) cells have a long history in the biopharmaceutical industry and currently produce the vast majority of recombinant therapeutic proteins. The key step in controlling process and product consistency is the development of a producer cell line derived from a single cell clone. However, it is recognised that genetic and phenotypic heterogeneity between individual cells in a clonal CHO population tends to arise over time. Previous bulk analysis of CHO cell populations has revealed considerable variation within the mtDNA sequence (heteroplasmy) which could have implications for the performance of the cell line. By analysing heteroplasmy of single cells within the same population, this heterogeneity can be characterised with greater resolution. Such analysis may identify heterogeneity in the mitochondrial genome which impacts the overall phenotypic performance of a producer cell population, and potentially reveal routes for genetic engineering. A critical first step is the development of robust experimental and computational methods to enable single cell mtDNA sequencing (termed scmtDNAseq). Here, we present a protocol from cell culture to bioinformatic analysis and provide preliminary evidence of significant mtDNA heteroplasmy across a small panel of single CHO cells.